Robotic Applications in Skiing: A Systematic Review of Current Research and Challenges - Boboc Răzvan Gabriel (My University, 2025)
This paper provides a comprehensive review of the current state of research on robotic technologies in sports, with a specific emphasis on skiing. Using a systematic review methodology, I conducted an extensive search for relevant academic articles and conference papers across several databases, including Scopus, Web of Science, and IEEE. A predefined set of keywords guided the search process, leading to an initial collection of 327 papers. After applying specific selection criteria, 24 studies were identified as most relevant to the topic. These selected works were analyzed in detail, covering various key aspects of robotics in skiing, from biomechanical modeling to robotic ski systems. The findings underscore the growing interest in this interdisciplinary field while also highlighting significant research gaps, particularly in stability control, real-time terrain perception, and snow–surface interaction. Overall, the review concludes that while promising developments exist, the field is still in its early stages and would benefit greatly from interdisciplinary collaboration and more robust real-world experimentation.